Xenogeneic human umbilical cord-derived mesenchymal stem cells reduce mortality in rats with acute respiratory distress syndrome complicated by sepsis - Lee, Fan-Yen (Oncotarget, 2017)
This study tested the hypothesis that xenogeneic human umbilical cord-derived mesenchymal stem cell (HUCDMSC) therapy would improve survival rates in rats with acute respiratory distress-syndrome (ARDS, induction by 48 h inhalation of 100% oxygen) and sepsis-syndrome (SS, induction by cecal-ligation and puncture) (ARDS-SS). Adult-male Sprague-Dawley rats were categorized into group 1 (sham-controls), group 2 (ARDS-SS), group 3 [ARDS-SS+HUCDMSC (1.2 ×10(6) cells administered 1 h after SS-induction)], and group 4 [ARDS-SS+HUCDMSC (1.2 ×10(6) cells administered 24 h after SS-induction)]. The mortality rate was higher in groups 2 and 4 than in groups 1 and 3 (all p<0.0001). The blood pressure after 28 h was lower in groups 2, 3 and 4 (p<0.0001) than in group 1. Albumin levels and percentages of inflammatory cells in broncho-alveolar lavage fluid, and the percentages of inflammatory and immune cells in circulation, were lowest in group 1, highest in group 2, and higher in group 3 than group 4 (all p<0.0001). The percentages of inflammatory cells in ascites and kidney parenchyma showed identical patterns, as did kidney injury scores (all p<0.0001). EarlyHUCDMSC therapy reduced rodent mortality after induced ARDS-SS.